(untitled) (Global Journal of Management and Business Research, 2019)
The previous literature documents stock market anomalies that challenge the Efficient Market Hypothesis (EMH), such as the January effect, weekend effect, ex-right day effect, exdividend effect, momentum, and reversal. In this paper, we provide additional international evidence on the existence of these anomalies in the Sweden stock market by using a unique panel dataset from 1912 to 1978. Our findings are important for understanding both the Sweden stock market and the Efficient Market Hypothesis (EMH).